Efektivitas Penambahan Auksin (IBA) dan Sitokinin (BAP) Terhadap Sambung Pucuk (Grafting) pada Pertumbuhan Vegetatif Tanaman Alpukat (Persea Americana) - Rafika Nasution; Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the effectiveness of auxin (IBA) and cytokinin (BAP) application on avocado (Persea americana) in improving grafting success. The method used was a factorial randomized block design (RBD) of 3×3 with three replications. The observed parameters included the percentage of graft survival, time to bud emergence, number of buds, bud length, and number of leaves. The results showed that the application of IBA and BAP significantly affected the time to bud emergence and bud length, but had no significant effect on the percentage of graft survival, number of buds, and number of leaves. In conclusion, growth hormones can accelerate the initial physiological response in grafting, although they do not always impact overall vegetative growth. Keywords: Avocado, BAP, Grafting, IBA, Persea americana